Geochemical analysis of obsidian from archaeological sites in northwestern Santa Cruz Province, Argentine Patagonia - Fernández, María Victoria (2015)
Obsidian raw material has been widely used in central and southern Patagonia from the beginning of the occupation of this region. In NW Santa Cruz province, Argentina, the geochemical analyses published to date suggest that Pampa del Asador was the main obsidian source. However, both the spatial and temporal limits of the distribution of obsidians from this and other sources in the region remain undefined. The principal goal of this article is to characterize obsidian artifacts from archaeological sites, located in a portion of NW Santa Cruz, from which there is no available geochemical information. ICP-MS analyses were obtained for 49 obsidian artifacts recovered from 24 excavated rockshelters and open-air surface scatters. The results indicate that all the samples of black obsidian came from the Pampa del Asador source, located ~90-160km to the south. Two samples of grey obsidian discovered on the top of Meseta del Lago Buenos Aires are chemically different from any other archeological obsidian yet analyzed in southern Patagonia. Their origin is still unknown, but they are most likely derived from a local Meseta del Lago Buenos Aires obsidian source. These results contribute to the knowledge about the use of obsidian in NW Santa Cruz, and provide constraints on the communication and material exchange between different environments and basins in this region.